Beliefs and perspectives on the future of oncology pharmacy—collated results of member surveys of the European Society of Oncology Pharmacy. Issue 1 (27th January 2023) - Crul, Mirjam; Meier, Carolin; Meier, Klaus
Abstract : Supplemental Digital Content is Available in the Text. Abstract: Introduction: The European Society of Oncology Pharmacy (ESOP) has nearly 4000 members in 66 countries. Periodically, the needs and interests of the members as well as the predictions of the members for the development of the profession of oncology pharmacy are mapped by the board of the Society. The aim of these inquiries is to help focus the Societies' advocacy works, knowledge exchange, and scientific and educational programs into those areas where the members deem this most needed. Methods: One survey into the future of oncology pharmacy was held in 12 individual countries during a national meeting on the topic of oncology pharmacy. In this survey, the forecasts of the members were researched. A second survey was held under the full membership to identify the topics of most interest within the broader field of oncology care. Results: Five hundred ninety-five colleagues responded to the future of oncology pharmacy survey and 757 to the topics of interest survey. Participating respondents came from 53 individual countries. Combined, the results show that both clinical care (in multiprofessional treatment teams) and education are important areas for the Society to continue paying attention to. The other important aspect of oncology pharmacy, which includes the practical and safety aspects of compounding, remains of great interest, especially regarding technical innovations such as robotics. Conclusion: ESOP will remain focused on its initial aim: to support optimal treatment for patients with cancer. The globally collated data from the two surveys show that both the clinical and the practical sides of the profession deserve continuing advancement.